Circular Economy in Retail Spaces: Behavioral Drivers Of Mall ‎Selection in Malaysia - Shina, Aminath; Wong, Ling Chai; Ahmad, Rohizan; Tee, Poh Kiong; Hasim, Halina; Wong, Siao Fui (International Journal of Accounting and Economics Studies, 2026)
Kuala Lumpur's retail sector, with revenue reaching $142.5 billion in August 2023, includes over 20 large shopping malls integrating Circular Economy (CE) practices to enhance sustainability. CE focuses on minimizing waste and maximizing resource efficiency through reusing, ‎recycling, and composting. This study examines the impact of CE initiatives on consumer behavior in these malls, utilizing primary data ‎from 614 respondents across 9–10 high-traffic malls. The research measures consumer awareness, preferences, engagement, loyalty, and ‎satisfaction with CE practices. Preliminary findings indicate that consumer awareness, engagement, and satisfaction significantly influence ‎mall selection, while preferences and loyalty show negligible impact. Applying the Theory of Planned Behavior, the study highlights the ‎importance of promoting environmental benefits, consumer responsibility, and empowering consumers through education and accessible ‎participation options. This research offers critical insights for mall developers, retailers, and policymakers, aiding them in aligning strategies ‎with growing consumer inclinations towards sustainability. By focusing on Kuala Lumpur, the study contributes a regional perspective to ‎the global discourse on sustainable retail, fostering a more environmentally responsible retail environment.
Keywords: Circular Economy (CE); Sustainability; Consumer Behavior; Recycling; Upcycling; Waste Management